Number and importance of somatic cells in goat’s milk - Lidija Kozačinski; T. Majić; Željka Cvrtila; Mirza Hadžiosmanović (Mljekarstvo)
Goat’s milk samples were examined on mastitis using stable procedure (California-mastitis test). 427 of the examined milk samples (46.82%) had positive reaction from 1 to 3 while other 485 samples (53.18%) had negative reaction on the mastitis test, indicating that no illness of mammary gland occurred. Number of somatic cells, counted using “Fossomatic” counter, was 1.3x106/ml average. By comparing the results of mastitis-test evaluation (CMT) with the number of somatic cells and findings of mastitis agents in milk showed that higher number of somatic cells is not the only indication of goat’s mammary gland illness. Mastitis-test is method that can exclude inflammation of goat’s mammary gland, but every positive reaction should be confirmed or eliminate with bacteriological examination. Based on the results of this research, it has been shown that the limit for somatic cells number in goat's milk can be over 1 000 000/ml.